The effect of online customer shopping experience on online impulsive buying mediated by attitudinal loyalty at E-commerce - Aprilyra, Nadila; Abror, Abror (Marketing Management Studies, 2024)
The purpose of this study was to determine the effect of online customer's shopping experience on online impulsive buying mediated by attitudinal loyalty on the Tokopedia e-commerce platform in Padang City. The population in this research are people in Padang City aged at least 18 years who have made purchases and have experience using the Tokopedia application. Data collection was carried out by distributing online questionnaires via G-Form and data was processed using SmartPLS software. The findings of this research show that (1) Interactivity has a positive but not significant effect on attitudinal loyalty, (2) Informativeness has a positive and significant effect on attitudinal loyalty, (3) Visual engagement has a positive and significant effect on attitudinal loyalty, (4) Navigation and search case does not have a positive and significant effect on attitudinal loyalty (5) Trust has a positive and significant effect on attitudinal loyalty, (6) Convenience has a positive but not significant effect on attitudinal loyalty, (7) Enjoyment has a positive and significant effect on attitudinal loyalty, (8) Attitudinal loyalty positive and significant effect on online impulsive buying, (9) Interactivity has a positive but not significant effect on online impulsive buying through attitudinal loyalty, (10) Informativeness has a positive and significant effect on online impulsive buying through attitudinal loyalty, (11) Visual engagement has a positive and significant effect on online impulsive buying significant effect on online impulsive buying through attitudinal loyalty, (12) Navigation and search case does not have a positive and significant effect on online impulsive buying through attitudinal loyalty, (13) Trust has a positive and significant effect on online impulsive buying through attitudinal loyalty, (14) Convenience has an effect positive but not significant on online impulsive buying through attitudinal loyalty, (15) Enjoyment has a positive and significant effect on online impulsive buying through attitudinal loyalty.